1990
DOI: 10.1136/jech.44.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and cause specific mortality in Athens.

Abstract: Study objective-The aim was to investigate the reported association between air pollution and cause specific mortaity in the city of Athens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0
6

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 24 publications
5
22
0
6
Order By: Relevance
“…However, several studies have not looked for lags of longer than 2 days. In a similar study, we observed earlier that sulfur dioxide and nitrogen dioxide, but not total suspended particulates or ozone, were associated with hospital admissions due to chronic bronchitis and emphysema in Helsinki.34 When sulfur dioxide was high, a significant peak of admissions was observed during the same day, but the strongest effect of nitrogen dioxide was delayed; after a small initial peak with a 1-to 3-day lag, it reached a second, statistically significant peak after 6 days. This may reflect a dual mechanism of the effect of pollutants.…”
supporting
confidence: 51%
“…However, several studies have not looked for lags of longer than 2 days. In a similar study, we observed earlier that sulfur dioxide and nitrogen dioxide, but not total suspended particulates or ozone, were associated with hospital admissions due to chronic bronchitis and emphysema in Helsinki.34 When sulfur dioxide was high, a significant peak of admissions was observed during the same day, but the strongest effect of nitrogen dioxide was delayed; after a small initial peak with a 1-to 3-day lag, it reached a second, statistically significant peak after 6 days. This may reflect a dual mechanism of the effect of pollutants.…”
supporting
confidence: 51%
“…In fact, many epidemiological studies demonstrated that air pollutants, like particulate matter, sulphur dioxide, and nitrogen oxides are related to acute and chronic respiratory effects [1][2][3][4][5][6][7][8][9][10][11], a decrease in pulmonary function [12][13][14][15], an increase in mortality from cardiovascular diseases and from lung cancer [16][17][18][19][20][21][22][23][24][25][26]. An excellent reanalysis of time-series studies on air pollution and health was recently published by the Health Effects Institute [27].…”
Section: Introductionmentioning
confidence: 99%
“…The ®nding of more pronounced eects on CVD mortality or possibly combined mortality from CVD or respiratory diseases con®rms the results of numerous investigations into cause-speci®c mortality [19,20,21] but are not fully in agreement with recently published data from the highly polluted North Bohemia region [4] where respiratory and CVD daily mortality were not always signi®cantly associated with air pollution, especially in people over 65 of age.…”
Section: Discussionmentioning
confidence: 54%